A method for preparing self-hardening spherical cement retarder using twin crystalline phosphogypsum

Through process control to obtain dual -crystal phospholosypsum that obtains low impurities, and use the semi -semi -semi -water sulfate of calcium glycogenic gypsum to prepare phosphopide spherical slowing agent to solve the problem of impurities and use in comprehensive utilization of phosphopide. Realize the preparation of high -quality, low -energy phospholosypsum spherical slowing agent.

CN116283015BActive Publication Date: 2025-01-28YIDU XINGFA CHEMICAL CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310163736.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-01-28
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

In the existing wet phosphoric acid production technology, the comprehensive utilization of phosphogypsum has problems such as impurities affecting performance and difficult to control powder use, resulting in high cost and complex process of phosphogypsum pretreatment.

Method used

Through process control, the dual -crystal phosphor gypsum is obtained through process control, and the crystal gelgropy of semi -water sulfate is used to prepare high -quality phospholly gypsum spherical slowing agents under low energy consumption and simple process conditions.

Benefits of technology

The low energy consumption and simplified process are achieved, and the high -quality, good liquidity phospholosypsum spherical slowing agent is obtained, the cost and energy consumption is reduced, and the problem of low success rate and poor liquidity is solved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of comprehensive utilization of phosphogypsum, and provides a method for preparing a self-hardening spherical cement retarder using twin crystalline phosphogypsum, wherein the twin crystalline phosphogypsum containing both calcium sulfate dihydrate and calcium sulfate hemihydrate is produced by controlling the wet phosphoric acid process, and the twin crystalline phosphogypsum is re-pulped, washed and improved to form balls, and then naturally hardened to obtain a spherical retarder. The present invention fully combines the green and low-energy wet phosphoric acid process advocated by the industry and the gelling effect of calcium sulfate hemihydrate itself, and obtains a spherical cement retarder with low impurity content and good fluidity without adding cement, steam curing, or turning the pile, which has significant significance for the green functional utilization of phosphogypsum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of comprehensive utilization of solid wastes in phosphorus chemical industry, and specifically is a method for producing twin crystalline phosphogypsum and preparing self-hardening spherical cement retarder by utilizing a wet phosphoric acid process. Background Art

[0002] Phosphoric acid dihydrate is currently the most widely used wet-process phosphoric acid production technology. However, with the requirements for green development of the phosphorus chemical industry, the semi-hydrate-dihydrate wet-process phosphoric acid production technology with lower energy consumption, higher phosphorus yield, and better quality of product acid and phosphogypsum has gradually been recognized, and its large-scale application has gradually increased. It has been listed as a green process to promote the transformation and upgrading of traditional industries.

[0003] Every ton of P2O5 produced by wet-process phosphoric acid will emit about 5 tons of phosphogypsum. Currently, strict requirements have been put forward for the green and comprehensive utilization of phosphogypsum. Compared with the traditional dihydrate method, the dihydrate phosphogypsum produced by the semi-hydrate-dihydrate method has high purity and is more conducive to comprehensive utilization. It is currently mainly used to prepare building gypsum powder, gypsum blocks, cement retarders, etc.

[0004] The use of phosphogypsum as a cement retarder is widely recognized. However, because harmful impurities in phosphogypsum affect its performance and the use process of powdered phosphogypsum is difficult to control, phosphogypsum is currently basically pre-treated before being supplied to cement processing units. Phosphogypsum pretreatment generally uses processes such as water washing, lime or alkaline calcium material neutralization, and the phosphogypsum powder is pelletized to improve its ease of use in the cement processing process.

[0005] Authorization announcement No. CN 109734344 B introduces the use of an alkaline calcium-containing modifier to adjust the semi-hydrated phosphogypsum to alkaline, and then modify the semi-hydrated phosphogypsum through processes such as aging and composting, so that the semi-hydrated phosphogypsum can be naturally crystallized into dihydrate gypsum under alkaline conditions for use as a cement retarder. Because its raw material is semi-hydrated gypsum, the dihydrate method and semi-hydrate-dihydrate method currently used on a large scale cannot directly produce semi-hydrated gypsum. If it is first crystallized into semi-hydrated gypsum, the cost will be relatively high.

[0006] Application publication number CN 110395929 A introduces a method of dry-mixing dihydrate gypsum and a modifier to adjust to alkalinity, and then entering a granulator for granulation; then the granulated material is loaded into an autoclave for autoclave reaction until the phosphogypsum is converted into hemihydrate gypsum, and after exiting the autoclave, during the cooling process, the hemihydrate gypsum is converted into dihydrate gypsum to become a cement retarder. After pelletizing, steam curing is used to convert the crystals into hemihydrate gypsum, and then water absorption is used to convert the crystals into dihydrate gypsum. The process is long and energy consumption is high.

[0007] In application publication number CN 113072318 A, phosphogypsum powder, cement and an improver are mixed and pelletized, and then the pellets are naturally stacked or autoclaved, and finally the pellets are slurried in cement slurry to obtain a high-strength phosphogypsum spherical retarder.

[0008] The present invention obtains low-impurity twin-crystal phosphogypsum through process control, and then utilizes the gelling property of hemihydrate calcium sulfate itself to achieve the hardening goal of phosphogypsum balls, and obtains high-quality, good fluidity phosphogypsum spherical retarder under low energy consumption and simple process. At the same time, the present invention solves the problem that the dry mixing effect of hemihydrate gypsum and modifier in authorization announcement number CN 109734344 B is poor and the reaction time is long, and the direct maturation and turning of the pile has more lumps and powders, resulting in a low balling rate and thus affecting the fluidity of the retarder. At the same time, the present invention can be organically combined with the green hemihydrate-dihydrate process that promotes the transformation and upgrading of the phosphorus chemical industry, and removes the restrictions on raw materials. Compared with application publication number CN 110395929 A, the present invention omits the steam curing process, does not require two crystal transformations to improve strength, and reduces process energy consumption. Compared with application publication number CN 110395929 A, the present invention does not need to use cement twice in the process, which reduces costs.

[0009] The present invention fully combines wet phosphoric acid process control with the preparation of spherical retarders, has low cost, short process, and the prepared spherical retarders have stable quality and good fluidity. The method of preparing self-hardening spherical cement retarders using twin crystalline phosphogypsum has been industrialized and has good promotion prospects. Summary of the invention

[0010] A method for preparing a self-hardening spherical cement retarder using twin crystalline phosphogypsum, the method comprising the following steps:

[0011] (1) fresh hemihydrate phosphogypsum dry residue and dihydrate phosphogypsum dry residue produced by wet-process phosphoric acid are uniformly mixed to obtain twinned phosphogypsum;

[0012] (2) re-slurrying the twin crystalline phosphogypsum of step (1), adding alkaline substances to adjust the pH, modifying it, and filtering it to obtain purified and improved twin crystalline phosphogypsum;

[0013] (3) The product obtained in step (2) is pelletized, and then naturally cured and hardened to obtain a spherical cement retarder.

[0014] The content of calcium sulfate hemihydrate in the twin crystalline phosphogypsum in step (1) is 5-50%.

[0015] The purpose of self-hardening of spherical phosphogypsum is achieved by utilizing the crystal transformation and gelling effect of calcium sulfate hemihydrate. At the same time, the water absorption and crystal transformation of calcium sulfate hemihydrate is utilized to further reduce the attached water content. If the content of calcium sulfate hemihydrate is too low, it will not have a gelling effect. If the content of calcium sulfate hemihydrate is too high, the self-hardening rate will be too fast, affecting the processing project. The optimal content of calcium sulfate hemihydrate in twin-crystalline phosphogypsum is 25%.

[0016] The water-soluble phosphorus pentoxide in the twin-crystalline phosphogypsum in step (1) has a mass fraction of 0.01%-0.30% for water-soluble phosphorus pentoxide, a mass fraction of 0.01%-0.15% for water-soluble fluorine, and a pH value of 3-6.

[0017] When the twin crystalline phosphogypsum is re-pulped in step (2), the solid content of the slurry is 10-40%, lime or carbide slag is added to control the pH value to 6-10, and aluminum sulfate as an activator is added at 1‰-10‰ of the dry basis of the phosphogypsum.

[0018] The pH value is further adjusted by adding lime or carbide slag, and the soluble phosphorus and fluorine that are difficult to remove by water washing are solidified. Lime is preferably added to the phosphogypsum slurry after digestion. The activator aluminum sulfate accelerates solidification and hardening. In order to avoid uneven mixing by adding directly to dry slag, aluminum sulfate is added to the phosphogypsum slurry at 1‰-10‰ of the dry basis of phosphogypsum. The most suitable addition ratio is 3‰-5‰, and the most suitable addition ratio is 5‰.

[0019] In the step (2), the water-soluble phosphorus pentoxide mass fraction of the twinned phosphogypsum after re-pulping, washing, purification and upgrading is less than 0.1%, the water-soluble fluorine is less than 0.03%, and the attached water content is 10-15%.

[0020] In the step (3), a disc granulator is used to form the pellets in one step, and the particle size is controlled to be 10-20 mm, or 10-20 mm accounts for at least 85% or more, and more preferably 10-20 mm accounts for at least 90% or more.

[0021] The natural curing and hardening time in step (3) is 3-5 days, during which time the pile does not need to be turned.

[0022] In the step (3), the mass fraction of water-soluble phosphorus pentoxide in the spherical retarder is less than 0.1%, the water-soluble fluorine is less than 0.03%, the attached water is less than 10%, the pH value is 6.5-9.5, the balling rate is greater than 90%, the proportion of particle size 10-20 mm is greater than 90%, and the crushing value is less than 20%.

[0023] The beneficial effects of the present invention are:

[0024] (1) Without the need to modify the semi-water-dihydrate device, high-quality twinned phosphogypsum can be obtained through process control. The original nature, water washing and slight modification are more conducive to ensuring the quality of phosphogypsum than using a large amount of alkaline calcium-containing substances, and are more beneficial to the addition ratio in cement processing and the quality control of cement;

[0025] (2) Taking advantage of the properties of the raw materials and adopting a self-hardening process, the artificial crystal transformation process is avoided, the energy consumption is low, the maintenance is simple, and the spherical retarder is more uniform in composition, avoiding quality fluctuations;

[0026] (3) Because the dry mixing modification process is eliminated, the unevenness of the raw materials for pelletizing is avoided, resulting in a high pelletizing rate, regular shape, and uniform strength, which is convenient for downstream use.

[0027] (4) The hydration of hemihydrate gypsum makes the ball harden while absorbing the attached water in the ball, reducing the free water content of the ball. DETAILED DESCRIPTION

[0028] The specific technical solutions of the present invention are further described below to help those skilled in the art further understand the present invention without limiting the rights thereof.

[0029] Example 1

[0030] In this embodiment, fresh calcium sulfate hemihydrate dry residue content of 4.5% and dihydrate phosphogypsum dry residue content of 95.5% are mixed, and the water-soluble phosphorus pentoxide mass fraction of the obtained twin phosphogypsum after mixing is 0.23%, the water-soluble fluorine mass fraction is 0.08%, and the pH value is 4.6; the twin phosphogypsum is re-slurried to a solid content of 30%, lime is added to adjust the pH value to 6.8, and aluminum sulfate is added at a ratio of 5‰ of the dry basis of the phosphogypsum, and the water-soluble phosphorus pentoxide mass fraction of 0.05% and the water-soluble fluorine mass fraction of 0.08% are obtained after pressure filtration. The purified and upgraded twin crystalline phosphogypsum has a fluorine mass fraction of 0.01% and an attached water content of 12.3%; the purified and upgraded twin crystalline phosphogypsum is formed into balls by a disc granulator; there is no need to turn the pile after balling, and after natural curing and hardening for 5 days, a spherical retarder product is obtained. The product has a water-soluble phosphorus pentoxide mass fraction of 0.05%, a water-soluble fluorine content of 0.01%, attached water of 10.5%, a pH value of 6.9, a balling rate of 73%, a particle size of 10-20 mm accounting for 74%, and a crushing value of 34%.

[0031] Example 2

[0032] In this embodiment, fresh calcium sulfate hemihydrate dry residue with a content of 25.2% and dihydrate phosphogypsum dry residue with a content of 74.8% are mixed, and the water-soluble phosphorus pentoxide mass fraction, the water-soluble fluorine mass fraction, and the pH value of the obtained twin phosphogypsum after mixing are 0.25% and 0.07%, respectively, and the pH value is 4.5; the twin phosphogypsum is re-slurried to a solid content of 30%, lime is added to adjust the pH value to 6.8, and aluminum sulfate is added at a ratio of 5‰ of the dry basis of the phosphogypsum, and after pressure filtration, a purified and upgraded twin phosphogypsum with a water-soluble phosphorus pentoxide mass fraction of 0.05%, a water-soluble fluorine mass fraction of 0.02%, and an attached water content of 12.4% is obtained; the purified and upgraded twin phosphogypsum is pelletized by a disc granulator;

[0033] There is no need to turn the pile after balling. After 2 days of natural curing and hardening, a spherical retarder product is obtained. The mass fraction of water-soluble phosphorus pentoxide in the product is 0.05%, the water-soluble fluorine content is 0.01%, the attached water is 10.3%, the pH value is 6.9, the balling rate is 88%, the particle size of 10-20mm accounts for 93%, and the crushing value is 30%.

[0034] There is no need to turn the pile after balling. After 4 days of natural curing and hardening, a spherical retarder product is obtained. The mass fraction of water-soluble phosphorus pentoxide in the product is 0.05%, the water-soluble fluorine content is 0.01%, the attached water is 9.8%, the pH value is 6.9, the balling rate is 91%, the particle size of 10-20mm accounts for 94%, and the crushing value is 15%.

[0035] There is no need to turn the pile after balling. After 6 days of natural curing and hardening, a spherical retarder product is obtained. The mass fraction of water-soluble phosphorus pentoxide in the product is 0.05%, the water-soluble fluorine content is 0.01%, the attached water is 9.8%, the pH value is 6.9, the balling rate is 92%, the particle size of 10-20mm accounts for 93%, and the crushing value is 12.8%. Extending the curing time has no effect on improving the quality of the product. Therefore, 4-5 days is reasonable based on reasonable time planning.

[0036] Example 3

[0037] In this embodiment, fresh calcium sulfate hemihydrate dry residue content of 33.6% and dihydrate phosphogypsum dry residue content of 66.4% are mixed, and the water-soluble phosphorus pentoxide mass fraction of the obtained twin crystalline phosphogypsum after mixing is 0.21%, the water-soluble fluorine mass fraction is 0.07%, and the pH value is 4.57; the twin crystalline phosphogypsum is re-slurried to a solid content of 30%, lime is added to adjust the pH value to 6.8, and aluminum sulfate is added at a ratio of 5‰ of the dry basis of the phosphogypsum, and the water-soluble phosphorus pentoxide mass fraction is 0.05% after pressure filtration. Purified and upgraded twin crystalline phosphogypsum with a water-soluble fluorine mass fraction of 0.01% and an attached water content of 13.7%; the purified and upgraded twin crystalline phosphogypsum is pelletized by a disc granulator; there is no need to turn the pile after pelletization, and a spherical retarder product is obtained after natural curing and hardening for 5 days, in which the mass fraction of water-soluble phosphorus pentoxide in the product is 0.03%, the content of water-soluble fluorine is 0.01%, the attached water is 9.9%, the pH value is 6.9, the balling rate is 97%, the particle size of 10-20mm accounts for 90%, and the crushing value is 7%.

[0038] Example 4

[0039] In this embodiment, fresh calcium sulfate hemihydrate dry residue content of 53.2% and dihydrate phosphogypsum dry residue content of 46.8% are mixed, and the water-soluble phosphorus pentoxide mass fraction of the obtained twin phosphogypsum after mixing is 0.27%, the water-soluble fluorine mass fraction is 0.08%, and the pH value is 4.5; the twin phosphogypsum is re-slurried to a solid content of 30%, lime is added to adjust the pH value to 6.8, and aluminum sulfate is added at a ratio of 5‰ of the dry basis of the phosphogypsum, and the water-soluble phosphorus pentoxide mass fraction of 0.05% and the water-soluble fluorine mass fraction of 0.08% are obtained after pressure filtration. The purified and upgraded twin crystalline phosphogypsum has a mass fraction of 0.01% and an attached water content of 13.7%. The purified and upgraded twin crystalline phosphogypsum is formed into balls by a disc granulator. There is no need to turn the pile after balling, and the spherical retarder product is obtained after natural curing and hardening for 5 days. The mass fraction of water-soluble phosphorus pentoxide in the product is 0.04%, the content of water-soluble fluorine is 0.01%, the attached water is 12.3%, the pH value is 6.9, the balling rate is 100%, the particle size is greater than 20mm, accounting for 91%, and serious agglomeration occurs during the curing process.

[0040] Example 5

[0041] In this embodiment, fresh calcium sulfate hemihydrate dry residue content of 25.2% and dihydrate phosphogypsum dry residue content of 74.8% are mixed, and the water-soluble phosphorus pentoxide mass fraction of the obtained twin phosphogypsum after mixing is 0.25%, the water-soluble fluorine mass fraction is 0.07%, and the pH value is 4.5; the twin phosphogypsum is re-slurried to a solid content of 30%, lime is added to adjust the pH value to 5.5, and aluminum sulfate is added at a ratio of 5‰ of the dry basis of the phosphogypsum, and the water-soluble phosphorus pentoxide mass fraction is 0.15%, the water-soluble fluorine mass fraction is 0.07%, and the pH value is 4.5. Purified and upgraded twin crystalline phosphogypsum with a soluble fluorine mass fraction of 0.06% and an attached water content of 12.8%; the purified and upgraded twin crystalline phosphogypsum is pelletized by a disc granulator; there is no need to turn the pile after pelletization, and a spherical retarder product is obtained after natural curing and hardening for 5 days. The product has a water-soluble phosphorus pentoxide mass fraction of 0.10%, a water-soluble fluorine content of 0.06%, attached water of 10.2%, a pH value of 5.9, a pelletization rate of 88%, a particle size of 10-20 mm accounting for 85%, and a crushing value of 26%.

[0042] Example 6

[0043] In this embodiment, fresh calcium sulfate hemihydrate dry residue content of 25.4% and dihydrate phosphogypsum dry residue content of 74.6% are mixed, and the water-soluble phosphorus pentoxide mass fraction of the obtained twin phosphogypsum after mixing is 0.26%, the water-soluble fluorine mass fraction is 0.07%, and the pH value is 4.6; the twin phosphogypsum is re-slurried to a solid content of 30%, lime is added to adjust the pH value to 8.8, and aluminum sulfate is added at a ratio of 5‰ of the dry basis of the phosphogypsum, and the water-soluble phosphorus pentoxide mass fraction is 0.01% after filtration. Purified and upgraded twin crystalline phosphogypsum with a soluble fluorine mass fraction of 0.01% and an attached water content of 12.3%; the purified and upgraded twin crystalline phosphogypsum is pelletized by a disc granulator; there is no need to turn the pile after pelletization, and a spherical retarder product is obtained after natural curing and hardening for 5 days. The product has a water-soluble phosphorus pentoxide mass fraction of 0.01%, a water-soluble fluorine content of 0.01%, attached water of 9.2%, a pH value of 8.9, a pelletization rate of 93%, a particle size of 10-20 mm accounting for 92%, and a crushing value of 19%.

[0044] Example 7

[0045] In this embodiment, fresh calcium sulfate hemihydrate dry residue content of 25.7% and dihydrate phosphogypsum dry residue content of 74.3% are mixed, and the water-soluble phosphorus pentoxide mass fraction of the obtained twin phosphogypsum after mixing is 0.26%, the water-soluble fluorine mass fraction is 0.07%, and the pH value is 4.6; the twin phosphogypsum is re-slurried to a solid content of 30%, lime is added to adjust the pH value to 11.1, and aluminum sulfate is added at a ratio of 5‰ of the dry basis of the phosphogypsum, and the water-soluble phosphorus pentoxide mass fraction is 0.01% after filtration. Purified and upgraded twin crystalline phosphogypsum with a soluble fluorine mass fraction of 0.01% and an attached water content of 12.1%; the purified and upgraded twin crystalline phosphogypsum is pelletized by a disc granulator; there is no need to turn the pile after pelletization, and a spherical retarder product is obtained after natural curing and hardening for 5 days. The product has a water-soluble phosphorus pentoxide mass fraction of 0.01%, a water-soluble fluorine content of 0.01%, attached water of 9.2%, a pH value of 11.0, a pelletization rate of 89%, a particle size of 10-20 mm accounting for 89%, and a crushing value of 23%.

[0046] Example 8

[0047] In this embodiment, fresh calcium sulfate hemihydrate dry residue content of 25.9% and dihydrate phosphogypsum dry residue content of 74.1% are mixed, and the water-soluble phosphorus pentoxide mass fraction of the obtained twin phosphogypsum after mixing is 0.28%, the water-soluble fluorine mass fraction is 0.08%, and the pH value is 4.5; the twin phosphogypsum is re-slurried to a solid content of 30%, lime is added to adjust the pH value to 6.8, and aluminum sulfate is added at a ratio of 0‰ on a dry basis of the phosphogypsum, and the water-soluble phosphorus pentoxide mass fraction is 0.02%, the water-soluble fluorine mass fraction is 0.08%, and the pH value is 4.5. Purified and upgraded twin crystalline phosphogypsum with a soluble fluorine mass fraction of 0.01% and an attached water content of 12.3%; the purified and upgraded twin crystalline phosphogypsum is pelletized by a disc granulator; there is no need to turn the pile after pelletization, and a spherical retarder product is obtained after natural curing and hardening for 5 days. The product has a water-soluble phosphorus pentoxide mass fraction of 0.02%, a water-soluble fluorine content of 0.01%, attached water of 9.3%, a pH value of 6.8, a pelletization rate of 78%, a particle size of 10-20 mm accounting for 69%, and a crushing value of 32%.

[0048] Example 9

[0049] In this embodiment, fresh calcium sulfate hemihydrate dry residue content of 25.9% and dihydrate phosphogypsum dry residue content of 74.1% are mixed, and the water-soluble phosphorus pentoxide mass fraction of the obtained twin crystalline phosphogypsum after mixing is 0.28%, the water-soluble fluorine mass fraction is 0.08%, and the pH value is 4.5; the twin crystalline phosphogypsum is re-slurried to a solid content of 30%, lime is added to adjust the pH value to 6.8, and aluminum sulfate is added at a ratio of 15‰ of the dry basis of the phosphogypsum, and the water-soluble phosphorus pentoxide mass fraction is 0.02% after pressure filtration. Purified and upgraded twin crystalline phosphogypsum with a water-soluble fluorine mass fraction of 0.01% and an attached water content of 12.3%; the purified and upgraded twin crystalline phosphogypsum is pelletized by a disc granulator; there is no need to turn the pile after pelletization, and a spherical retarder product is obtained after natural curing and hardening for 5 days. The product has a water-soluble phosphorus pentoxide mass fraction of 0.02%, a water-soluble fluorine content of 0.01%, attached water of 9.2%, a pH value of 6.9, a pelletization rate of 86%, a particle size of 10-20 mm accounting for 89%, and a crushing value of 24%.

Claims

1. A method for preparing a self-hardening spherical cement retarder using twin crystalline phosphogypsum, characterized in that: The method steps are as follows: The content of fresh hemihydrate calcium sulfate dry residue is 33.6%, and the content of dihydrate phosphogypsum dry residue is 66.4%. The water-soluble phosphorus pentoxide mass fraction of the obtained twin crystalline phosphogypsum after mixing is 0.21%, the water-soluble fluorine mass fraction is 0.07%, and the pH value is 4.57; the twin crystalline phosphogypsum is re-slurried to a solid content of 30%, lime is added to adjust the pH value to 6.8, and aluminum sulfate is added at a ratio of 5‰ of the dry basis of the phosphogypsum, and the water-soluble phosphorus pentoxide mass fraction of 0.05% and the water-soluble fluorine mass fraction of 0.07% are obtained after filtering. The purified and upgraded twin crystalline phosphogypsum has a fluorine mass fraction of 0.01% and an attached water content of 13.7%; the purified and upgraded twin crystalline phosphogypsum is formed into balls by a disc granulator; there is no need to turn the pile after balling, and after natural curing and hardening for 5 days, a spherical retarder product is obtained. The product has a water-soluble phosphorus pentoxide mass fraction of 0.03%, a water-soluble fluorine content of 0.01%, attached water of 9.9%, a pH value of 6.9, a balling rate of 97%, a particle size of 10-20mm accounting for 90%, and a crushing value of 7%.

Citation Information

Patent Citations

  • A method for preparing cement retarder using hemihydrate phosphogypsum

    CN109734344B

  • Phosphogypsum modified cement retarder

    CN110395929A

  • Spherical phosphogypsum as well as preparation method and application thereof

    CN113072318A

  • Cement retarder and method for direct preparation of same by using semi-hydrated phosphogypsum

    CN102351453A

  • Phosphogypsum ball and preparation method and application thereof

    CN103482896A